Pandoraea pulmonicola chronic colonization in a cystic fibrosis patient, France. Issue 2 (30th September 2013) - Kokcha, S.; Bittar, F.; Reynaud‐Gaubert, M.; Mely, L.; Gomez, C.; Gaubert, J.‐Y.; Thomas, P.; Rolain, J.‐M.
Abstract: Pandoraea are considered emerging multidrug resistant pathogens in the context of cystic fibrosis. We report herein for the first time the case of a 30‐year‐old woman with cystic fibrosis, living in France, who was chronically infected with Pandoraea pulmonicola and who died of Pseudomonas aeruginosa sepsis 3 weeks after bilateral lung transplantation.